COP27 and the path to implementing the Paris Agreement targets: opportunities and critical issues in the light of the establishment of the Loss and Damage Fund (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
COP27 established the Loss and Damage Fund to compensate the countries most affected by the negative effects of climate change. The Fund can only be activated for the benefit of materially vulnerable states and not also for the benefit of individuals: this is a step forward in terms of solidarity between states, but not between individuals. This situation leads to two considerations: firstly, the principle of solidarity should be understood both horizontally (between present) and vertically (towards future generations). Moreover, the Fund does not solve the critical issues of individual access to climate justice.
Keywords: Climate change; Loss & Damage; intergenerational solidarity; climate justice; climate litigation